SECONDARY SKIN SYPHILIS AND MUCOUS MEMBRANES AT ELEVEN-MONTHLY PATIENT - Sergey V. Koshkin; Anna L. Evseeva; Vera V. Ryabova; Ol'ga S. Kovrova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The current article analyzes a clinical case of insontium syphilis (secondary syphilis) in a 11-month patient. Attention is paid to household path of transmission of syphilis from parents to their child. Problems of differential diagnosis for clinical evidence of secondary acquired syphilis and congenital syphilis were analyzed.